Factor VIII Intron 22 Inversion in Severe Hemophilia A Patients in Palestine - Caesar Mahmoud Abu Arra; Fekri Samarah; Nael Sudqi Abu Hasan (Scientifica)
Background. Hemophilia A is an X-linked recessive bleeding disorder caused by mutations in FVIII gene with an incidence of 1 in 5,000 to 10,000 live born males. The Inv22 mutation is a major cause of the disease worldwide, accounting for up to 40%–50% of severe FVIII mutations. The aim of the present study was to screen Inv22 of the FVIII gene in Palestinian patients with severe HA and reveal its role as a predisposing factor for the development of inhibitors. Materials and Methods. A cohort of 77 HA individuals including 5 carrier females from 52 unrelated families registered at governmental hemophilia centers in the West Bank area of Palestine was investigated. The demographic data and the clinical history were retrieved from medical files. Molecular analysis of Inv22 mutation in severe HA (30 cases) from Palestine was performed using the subcycling polymerase reaction (S-PCR). FVIII coagulant activities were carried out on an aPTT-based 1-stage clotting assay. FVIII inhibitors were quantified using the Nijmegen modification of the Bethesda assay. Result. Overall, 41.7% (30/72) of the studied cases were classified as having severe HA, 22.2% (16/72) had moderate HA, and 36.1% (26/72) had mild HA. Five randomly selected carrier mothers were screened for the Inv22 mutation to confirm its transmission to their sons. The Inv22 mutation was detected in 11 severe HA patients (36.6%). Among the severe HA patients with positive Inv22, 45.5% (5/11) had developed inhibitors. The current study showed that there was no association (p=0.53) between inhibitor development and the Inv22 mutation. Conclusion. Findings on Inv22 are in agreement with worldwide reports, being a major genetic mutation in severe HA. The S-PCR is a simple, rapid, and cost-effective method for the diagnosis of Inv22 in severe HA patients. Although the Inv22 mutation was associated with 36.6% of severe HA phenotype cases, it was not a major predisposing factor for inhibitor formation.